2022
DOI: 10.1097/bpo.0000000000002187
|View full text |Cite
|
Sign up to set email alerts
|

Sacral-Alar-Iliac (SAI) Fixation in Children With Spine Deformity: Minimum 10-Year Follow-Up

Abstract: Introduction: Sacral-alar-iliac (SAI) screws are utilized to achieve pelvic fixation in spine deformity patients. The primary purpose of this study is to investigate the long-term outcomes of pediatric patients with scoliosis treated with posterior spinal fusion and SAI fixation at 10-year clinical and radiographic follow-up. Methods: We reviewed the clinical and radiographic records of patients aged 18 years or below treated for scoliosis with posterior spinal fusion using SAI fixation. Pelvic obliquity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Винты S2-alar-iliac являются безопасным и эффективным методом фиксации таза у детей с деформацией позвоночника. Результаты через ≥ 10 лет являются удовлетворительными, с низким уровнем отдаленных осложнений и отличной послеоперационной коррекцией и последующим поддержанием фронтального баланса и наклона таза с течением времени [10,11].…”
Section: результаты исследования и их обсуждениеunclassified
“…Винты S2-alar-iliac являются безопасным и эффективным методом фиксации таза у детей с деформацией позвоночника. Результаты через ≥ 10 лет являются удовлетворительными, с низким уровнем отдаленных осложнений и отличной послеоперационной коррекцией и последующим поддержанием фронтального баланса и наклона таза с течением времени [10,11].…”
Section: результаты исследования и их обсуждениеunclassified
“…Their safety and long-term efficacy were supported by a series by Mun et al with a minimum 10-year follow-up in which the authors reported a 2% reoperation rate. All reoperations were for the management of late deep infections 20 . It should be noted that many patients develop some lucency around the screw (>2 mm).…”
Section: Spinementioning
confidence: 99%
“…The starting point of an SAI screw is medial to the posterior superior iliac spine below the iliac level, which results in fewer soft tissue problems. Moreover, to date, it has not yet been reported that notable neurovascular or visceral complications from the screws in the setting of spinal deformity or pelvic osteotomy surgery 10,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to date, it has not yet been reported that notable neurovascular or visceral complications from the screws in the setting of spinal deformity or pelvic osteotomy surgery. 10,12,13 To date, however, few studies have examined SAI screws for SI joint dislocation. To end this, a finite element analysis was performed to compare the stability of SI screw fixation and SAI screws for SI joint dislocation to provide a reference for clinical practice.…”
Section: Introductionmentioning
confidence: 99%